Early Acquisition of Lexicon: Language Universals vs. Language Specificities - Kovačević, Melita; Babić (Jelaska), Zrinka (1996)
The topic of lexical acquisition has gained more attention only recently. The acquisition of syntax has been studied more profoundly - while numerous highly structured principles were recognized as a base for syntax acquisition, no such principles were defined regarding lexicon acquisition. Linguistic inquiries of the last decade show that the lexicon is much more structured than it was believed, and that neither words' perception nor their learning is simple. This paper will discuss some aspects of early lewicon acquisition in children from 8 to 36 months, namely the appearance of different word categories in a child's first vocabulary. A contrastive analysis of some relevant examples from Croatian and English will be presented. The authors will argue that both cultural/contextual and structural factors have an impact on lexicon acquisition. Bearing in mind that syntactic and lewical structure are so closely entwined, we should consider those linkages while considering the process of learning words.
Projekt MZOS
ENG